Development of organisational culture to ensure community security - Zelenschi, Angela (Ukrainian Cultural Studies, 2022)
This article explores the concept of organisational culture as a strategic tool that can be used by leaders to undertake the organisational changes necessary to ensure community security. Managers' actions are primarily geared toward the functioning of the organization as an entity, towards increasing employee engagement in achieving organizational goals, and secondly, actions are externally oriented, being focused on establishing a network of relationships with community stakeholders to achieve goals and promote organizational causes. Theoretical research on the phenomenon of organizational culture is carried out, using the method of examining the correlations between the elements of organizational management – organizational culture and organizational leadership, organizational culture and external networks, organizational culture, and effective habits of employees. The author addresses the problem of developing organisational culture within the police with the aim of improving the management system. The outcomes achieved by the author can be applied in theoretical research on organizational culture, in the managerial process of police structures, and in the training process of young specialists in the field of security and public order.
Keywords: organisational culture; values; effective skills; interdependent networks; community security